Exploration of severe early childhood caries microbiota through a novel developed nutrient enriched microbiological medium, high through-put 16S rRNA sequencing and culturomics - Yixin Zhang; Yang Chen; Chang Diao; Haojie Lin; Jingqi Zhu; Ruiqing Sun; Meng Wang; Yuke Chen; Hanzhang Zhou; Zixi Dong; Bin Xia; Yixiang Wang (PeerJ)
Introduction Severe early childhood caries (S-ECC) is a widespread disease that harms children physically and mentally. Microorganisms are regarded as the dominant etiology of caries, however, S-ECC microbiome remains largely unknown, nearly 1/4 of them remained uncultivated. To explore S-ECC microbiota, a new bacterial medium, nutrient-enriched microbiological medium (NEMM) was designed in this study. Methods Eleven fresh S-ECC dental plaque samples were collected and cultivated in both NEMM and SHI medium (reference medium) for 0, 1, 3, 6, 9, 15, 21 and 28 days under aerobic and anaerobic conditions. Thereafter, the cultures were harvested, together with their corresponding clinical S-ECC dental plaque samples, for high through-put 16S rRNA sequencing and culturomics. The single colonies were cultured for further confirmation by sequencing the full length of the 16S rRNA gene after bacterial genomic DNA extraction and PCR amplification. Results Either NEMM or SHI medium showed a significant decrease in bacterial alpha diversity compared to clinical dental plaque samples by high throughput 16S rRNA sequencing analysis, indicating a larger room for the improvement of both media. NEMM displayed more living bacteria, abundant bacteria species, uncultured bacteria and capacities in carbohydrate transport and metabolism than SHI medium. The dynamic changes in bacterial community composition over time indicated that some bacteria tended to be enriched at specific time points. Culturomics and identification of bacterial species results were further confirmed by the high throughput 16S rRNA sequencing results. Conclusion We developed a new medium NEMM that could support S-ECC microbiota growth with a higher yield of living bacteria, higher abundance and capacity, and be suitable for cultivating oral uncultured bacteria via culturomics technology.